Power Scaling of a Narrowband-Seeded PPLN Non-Resonant Optical Parametric Oscillator - Temel,T; Murray,RT; Wang,L; Chen,W; Schirrmacher,A; Battle,RA; Petrov,V (2023)
A PPLN non-resonant optical parametric oscillator injection-seeded by narrowband sub-100-mW CW radiation at the signal wavelength produces > 3 W idler average power at 2376 nm for a 20-kHz repetition rate, with sub-2-nm spectral linewidth.